Peculiarities of controlling an emergency situation on a water vehicle - Azarenko , Olena; Goncharenko , Yuliya; Divizinyuk , Mykhailo; Mirnenko, Volodimir; Farrakhov , Oleksandr (Social Development and Security, 2019)
Based on an analysis of the main approaches to describing the emergency management process and the regularity of an emergency as a spatio-temporal process, it is proposed to use the concept of risk as one of the criteria used to evaluate the effectiveness of emergency management on a water vehicle. The purpose of this work is to determine the peculiarities of the management of the NA on a water vehicle in the inland and territorial waters of Ukraine. In order to achieve this, the main approaches to the description of the emergency management process are analyzed, the regularities of the emergency situation as a space-time process are considered, and the use of the concept of risk as one of the criteria used to evaluate the effectiveness of emergency management on a water vehicle is proposed. The work assesses the possibility of dangerous phenomena by means of risk. These phenomena include natural, man-made, social, economic phenomena that occur in nature, technosphere, society, economy and are the result of the development of relevant processes. The development of these processes lead to the formation in the environment of negative (harmful, adverse) impacts on the population, objects of the technosphere and the natural environment, worsen the conditions of activity for socio-economic systems. Individual interests of people (organizations) are satisfied within separate systems of activity. These may include a person and a set of environmental objects that interact to achieve a specific human interest. The processes of life and activity in relation to people and organizations have properties, the most important of which is danger and safety. Based on the results obtained, it is proved that the level of risk of a catastrophic event is a qualitative assessment of emergency management on a water vehicle in the initial sex, and in the future the effectiveness of emergency management is assessed by the degree of minimization of the consequences of the catastrophic event.